Blood-brain barrier disturbances in diabetes-associated dementia: Therapeutic potential for cannabinoids - Brook, E.; Mamo, John; Wong, R.; Al-Salami, Hani; Falasca, Marco; Lam, Virginie; Takechi, Ryu (Academic Press, 2019)
© 2019 Elsevier Ltd Type-2 diabetes (T2D) increases the risk of dementia by ˜5-fold, however the mechanisms by which T2D increases dementia risk remain unclear. Evidence suggests that the heightened inflammation and oxidative stress in T2D may lead to disruption of the blood-brain barrier (BBB), which precedes premature cognitive decline. Studies show that vascular-targeted anti-inflammatory treatments protect the BBB by attenuating neuroinflammation, and in some studies attenuate cognitive decline. Yet, this potential pathway is understudied in T2D-associated cognitive impairment. In recent years, therapeutic potential of cannabinoids has gained much interest. The two major cannabinoids, cannabidiol and tetrahydrocannabinol, exert anti-inflammatory and vascular protective effects, however few studies report their potential for reversing BBB dysfunction, particularly in T2D. Therefore, in this review, we summarize the current findings on the role of BBB dysfunction in T2D-associated dementia and consider the potential therapeutic use of cannabinoids as a protectant of cerebrovascular BBB protection.